Determining The Correlation Between Adolescent Attitudes and Practices in Sexual and Reproductive Health - Putri, Angga; Sansuwito, Tukimin bin (Health Science UDINUS, 2025)
Adolescents often show gaps between their attitudes and practices regarding sexual and reproductive health, which can affect their overall wellbeing and decision-making. Understanding these correlations between attitudes and behaviors is critical to developing effective educational interventions and health policies to improve adolescent health outcomes. This study aims to identify the relationship between attitudes and adolescent practices regarding sexual and reproductive health. This study is quantitative. It uses two analytical tests, namely descriptive analysis to see the distribution of variables and a correlation statistical test to see the relationship between variables. Respondents of 179 students were randomly taken at each level. The questionnaire was distributed using a Google form to measure variables. Most respondents were female, 60.9% (n=109), with most being 16 years old, 27.9% (n=50). Grade XII students filled out the questionnaire the most, 44.1% (n=79). A statistically significant relationship was found between adolescents' attitudes and practices regarding sexual and reproductive health (p=0.04). Based on these findings, adolescent sexual and reproductive health education programs can be designed more effectively to adjust to the content and attitude approach according to their needs. The educational program focuses on behavior change with topics relevant to adolescents, using interactive methods, group dynamics, and peer approaches. With the selection of the right approach, it is hoped that it can increase knowledge, develop attitudes, and ultimately direct positive behavior in adolescents towards sexual and reproductive health.